A comparative study on a newly designed ball mill and the conventional ball mill performance with respect to the particle size distribution and recirculating load at the discharge end. (1st January 2020) - Hanumanthappa, Harish; Vardhan, Harsha; Mandela, Govinda Raj; Kaza, Marutiram; Sah, Rameshwar; Shanmugam, Bharath Kumar
Graphical abstract: Highlights: Lifters with primary, secondary and tertiary plates were used at discharge end. Discharge of desired particle size is directly related to critical speed of the mill. Mill with lifters has maximum discharge of desired particle size. Mill with lifters has minimum recirculating load compared with mill without lifters. Abstract: The discharge end design of a ball mill plays an important role in discharging the desired particle sizes (−150 + 10 µm) and the percentage of recirculating load from the discharge end of the ball mill. In continuous wet ball mills, the composition of feed (hard ore or soft ore) to the mill varies continuously, leading to uncontrolled grinding in the mill. In view of this, a new design of the discharge mechanism has been implemented to remove the ground particles of desired particle size fraction with minimum recirculating load (+150 µm). The results from the discharge end with lifters (closed and open) show that the particle size fraction obtained from the discharge end has a maximum percentage of desired particle size fraction when the mill is operating at 60% critical speed. Discharge end without lifters has an uncontrolled particle size distribution in the discharge and the percentage of desired-size particles discharged was found to be very less. Also, the percentage of the recirculating load is minimum in the case of discharge end with lifter design compared with discharge end without a lifter. Hence, a new design of lifters in the discharge end leads to the discharge of the desired particle size fraction with minimum recirculating load.